Chryseobacterium indologenes carrying blaIND-1 isolated from blood obtained from a patient with adenocarcinoma: a case report and minireview of the literature. Issue 3 (July 2015) - Ojdana, Dominika; Gińdzieńska-Sieśkiewicz, Ewa; Sacha, Paweł; Wieczorek, Piotr; Krawczyk, Malgorzata; Kita, Karol; Michalska, Anna; Sierakowski, Stanisłlaw; Tryniszewska, Elżbieta
Abstract : Chryseobacterium indologenes is an environmental organism and is an uncommon human pathogen. This causes opportunistic infections in patients with severe underlying clinical conditions. C. indologenes infections are problematic because of decreased therapeutic options attributable to bacterial resistance to antibiotics, which mainly depend on the production of the specific IND type of metallo-β-lactamases. We report a case of C. indologenes in a blood sample obtained from a patient with adenocarcinoma. The patient was treated with a 1.2-g dose of Augmentin three times a day. The treatment was followed by normalization of the patient's temperature. The patient was finally transferred to the surgery department for further investigation. Molecular biology revealed that the tested strain carried the bla IND-1 gene, which is responsible for the production of the IND-1 type of metallo-β-lactamase. To the best of our knowledge, this is the first description of IND-1-producing C. indologenes bacteraemia in Poland.